Câmbio real do Brasil: determinantes de longo prazo: evidências a partir de testes não paramétricos de cointegração e de tendência não linear comum - Paiva, Luciano Dias (2011)
The paper seeks the existence of a cointegration relation among the Real Exchange Rate (CRER), Net Foreign Assets (PEL), Terms of Trade (TOT) and a productivity measure (BS), using a nonparametric test proposed by Bierens (1997), applied to an U.S. and Brazil data sample, considering the period that goes from 1980 to 2010. For the U.S., evidence of those variables’ influence is found. In the Brazilian case, little relevance from the BS variable is verified, while the remaining ones are relevant to the cointegrating vector.